Development of Chitosan-Polyacrylic Acid Complex Systems for Enhanced Oral Delivery of Lactobacillus Gasseri and Bifidobacterium Bifidum Probiotics - AL-Fawares O; Alshweiat A; Abuawad A (Drug Design, Development and Therapy)
O’la AL-Fawares,1 Areen Alshweiat,2 Alaa Abuawad3 1Department of Applied Biological Sciences, Faculty of Science, Al-Balqa Applied University, Al-salt, 19117, Jordan; 2Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmaceutical Sciences, The Hashemite University, Zarqa, 13133, Jordan; 3Department of Pharmaceutical Sciences and Pharmaceutics, Faculty of Pharmacy, ‎Applied ‎Science Private University, Amman, 11937, JordanCorrespondence: O’la AL-Fawares, Department of Applied Biological Sciences, Faculty of Science, Al-Balqa Applied University, P.O. Box 206, Al-salt, 19117, Jordan, Tel +9627997622457, Email ola.alfawares@bau.edu.joIntroduction: The beneficial effects of probiotics are encountered by their low viability in gastrointestinal conditions and their insufficient stability during manufacturing, throughut the gastrointestinal transit, and storage. Therefore, novel systems are highly required to improve probiotics delivery.Methods: In this study, Lactobacillus gasseri (L), Bifidobacterium bifidum (B), and a combination of L+B were encapsulated in chitosan (CS)-polyacrylic acid (PAA) complex systems (CS-PAA). The CS-PAA systems were analysed on basis of morphology, size, and zeta potential. The loaded CS-PAA systems were evaluated for their morphology, particle size, zetapotential, vaiability in both simulated gastroic and intestinal fluids, and stability at 4°C storage temparature. Moreover, the antibiofilm activity of the probiotics-loaded systems were evaluated againt Campylobacter jejuni, Pseudomonas aeruginosa and Escherichia coli.Results: Probiotic strains were successfully incorporated into the porous structures of the CS-PAA systems, either individually or in combination. The Loaded L, B, and L+B showed higher particle size than the unloaded particles and excellent viability in simulated gastric and intestinal fluids, where the free probiotic species were undetected. Additionally the loaded probiotic exhibited an anti-biofilm effect at 0.5 mg/mL concentration level.Conclusion: The CS-PAA complexes demonstrate a promising mechanism for the effective delivery of incorporated probiotics. The probiotics exhibited high viability and maintain stability under physiological conditions, and showed a remarkable anti-biofilm activity. These characteristics suggest that CS-PAA could serve as an alternative system for probiotics, enhancing gut microbiota health and offering a robust protection against microbial pathogens.Keywords: probiotics, Lactobacillus gasseri, Bifidobacterium bifidum, chitosan, encapsulation, polyacrylic acid